The differences in drug disposition gene induction by rifampicin and rifabutin are unlikely due to different effects on important pregnane X receptor (NR1I2) splice variants - Nilles, Julie; Weiß, Johanna; Masin, Martin; Tuffs, Christopher; Strowitzki, Moritz; Haefeli, Walter E.; Ruez, Stephanie; Theile, Dirk (Naunyn-Schmiedeberg's archives of pharmacology, 2023)
Rifampicin and rifabutin can activate the pregnane X receptor (PXR, NR1I2), thereby inducing pharmacokinetically important genes/proteins and reducing exposure to co-administered drugs. Because induction effects vary considerably between these antibiotics, differences could be due to unequal rifamycin-induced activation or tissue expression of the three major NR1I2 splice variants, PXR.1 (NM_003889), PXR.2 (NM_022002), and PXR.3 (NM_033013). Consequently, PXR activation (PXR reporter gene assays) and mRNA expression levels of total NR1I2, PXR.1, PXR.2, and PXR.3 were investigated by polymerase chain reaction in colon and liver samples from eleven surgical patients, in LS180 cells, and primary human hepatocytes. Compared to the colon, total NR1I2 mRNA expression was higher in the liver. Both tissues showed similar expression levels of PXR.1 and PXR.3, respectively. PXR.2 was not quantifiable in the colon samples. Rifampicin and rifabutin similarly enhanced PXR.1 and PXR.2 activity when transfected into LS180 cells, while PXR.3 could not be activated. In LS180 cells, rifampicin (10 μM) reduced total NR1I2 and PXR.3 expression 2-fold after 24 h, while rifabutin (10 μM) increased total NR1I2, PXR.1, PXR.2, and PXR.3 mRNA by approx. 50% after 96-h exposure. In primary human hepatocytes, rifampicin (10 μM) suppressed total NR1I2, PXR.1, and PXR.3 after 48-h exposure, and rifabutin (10 μM) had no significant impact on total NR1I2 or any of the splice variants studied. In conclusion, both antibiotics activated the studied PXR splice variants similarly but modified their expression differently. While rifampicin can suppress mRNA of PXR forms, rifabutin rather increases their expression levels.
Gesehen am 29.11.2023